RESPON EMOSIONAL SEBAGAI MEDIASI PENGARUH VISUALISASI DESAIN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN Studi Kasus Pada Pembeli Rokok Sampoerna A Mild di Warung Kopi Waris Tulungagung - Shidiqy, Dhiyau (An-Nisbah: Jurnal Ekonomi Syariah, 2016)
The present study aims at determining the effect of packaging design visualization on customersâ purchasing decision by employing emotional response as mediator variable. The data were collected through questionnaires. Meanwhile, the population of the present study is the customersâ of Sampoerna A mild at Warung Kopi Waris Tulungagung and 110 customers were taken as sample. The sample measurement guideline employed is Maximum Likehood technique with simple random sampling technique. At the same time, the data analysis employed is structural equation modeling. The result of the study indicates packaging design visualization has negative and insignifcant effect on purchasing decision of Sampoerna A mild. Packaging design visualization of Sampoerna A Mild has positive and insignifcant effect on emotional response. Emotional response has positive and signifcant effect on purchasing decision of Sampoerna A mild. Emotional response does not mediate the effect of packaging design visualization of Sampoerna A Mild on customersâ purchasing decision.Key words: packaging design, emotional responses, purchasing